2011
DOI: 10.1103/physrevb.83.024407
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of 3dtransition-metal monolayers on Rh(100)

Abstract: We employ the full-potential linearized augmented plane-wave method to report a systematic density-functional theory study of the magnetic properties of the 3d transition-metal (V, Cr, Mn, Fe, Co, and Ni) monolayers deposited on the Rh(100) substrate. We find that all monolayer films are magnetic. The size of the local magnetic moments across the transition-metal series follows Hund's rule with a maximum magnetic moment of 3.77μ B for Mn. The largest induced magnetic moment of about 0.46μ B was found for Rh at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…The change from FM to AFM order of the Fe monolayers deposited on Ag(001) or W(001) can then be attributed to a change in sign of the nearestneighbor coupling constant, J 1 , by the substrate through its hybridization with the monolayer [8]. Similar trends were found for 4d TMs in (111) and (001) orientation [9,10]. If the influence of the substrate is tuned such that Heisenberg interactions between two spins, also named two-spin interactions, become small, higher-order spin interactions such as the biquadratic term or cyclic 4-spin exchange become important [11,12].…”
supporting
confidence: 68%
“…The change from FM to AFM order of the Fe monolayers deposited on Ag(001) or W(001) can then be attributed to a change in sign of the nearestneighbor coupling constant, J 1 , by the substrate through its hybridization with the monolayer [8]. Similar trends were found for 4d TMs in (111) and (001) orientation [9,10]. If the influence of the substrate is tuned such that Heisenberg interactions between two spins, also named two-spin interactions, become small, higher-order spin interactions such as the biquadratic term or cyclic 4-spin exchange become important [11,12].…”
supporting
confidence: 68%
“…17 The films are modeled by a symmetric seven-layer Rh(001) slab covered by 3d transition-metal monolayers (ML) on each side, using the calculated Rh in-plane lattice constant 3.819Å in Ref. 5. The plane wave (PW) cutoff parameter is chosen as k max = 7.56Å −1 with a muffin-tin sphere radius of R MT = 1.22Å for the 3d atoms and 1.28Å for the Rh atoms.…”
Section: Computational Detailsmentioning
confidence: 99%
“…4 3d transition metal monolayers on rhodium substrate have been systematically investigated within ab initio calculations in Ref. 5: The magnetic order was found to be ferromagnetic for Co whereas Fe favors an antiferromagnetic (AFM) ground state. In addition, calculations of the magnetic anisotropy energy (MAE) showed that the magnetization of both Fe and Co is oriented in-plane.…”
Section: Introductionmentioning
confidence: 99%
“…From previous experimental studies it is not clear whether zero net magnetization states, such as antiferromagnetism or a complex non-collinear state, exist in ultrathin Fe films. Theoretical calculations were carried out by two independent groups [8,9] and it was reported that 1 ML Fe films show a c(2 Â 2) antiferromagnetic state with an in-plane magnetic anisotropy. To reveal the local magnetic ordering, it is necessary to study Fe films with a method sensitive to atomic-scale magnetic structures.…”
Section: Introductionmentioning
confidence: 99%